Risk factors and outcome of Chimeric Antigen Receptor T-Cell patients admitted to Pediatric Intensive Care Unit: CART-PICU study - Caballero-Bellón, Marina; Alonso-Saladrigues, Anna; Bobillo-Perez, Sara; Faura, Anna; Arqués, Laura; Rivera, Cristina; Català, Albert; Dapena, Jose Luis; Rives, Susana; Jordan, Iolanda (Frontiers in Immunology, 2023)
Introduction: Chimeric antigen receptor (CAR)T-cell CD19 therapy is an effective treatment for relapsed/refractory B-cell acute lymphoblastic leukemia. It can be associated with life-threatening toxicities which often require PICU admission. Purpose: to describe clinical characteristics, treatment and outcome of these patients.Methods: Prospective observational cohort study conducted in a tertiary pediatric hospital from 2016-2021. Children who received CAR-T admitted to PICU were included. We collected epidemiological, clinical characteristics, cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS), treatment, length of stay and mortality.Results: CAR T-cells (4-1BB constructs) were infused in 59 patients. Twenty-four (40.7%) required PICU admission, length of stay was 4 days (IQR 3-6). Median age was 8.3 years (range 4-24). Patients admitted to PICU presented higher disease burden before infusion: 24% blasts in bone marrow (IQR 5-72) vs. 0 (0-6.9), p<0.001. No patients with <5% blasts were admitted to PICU. Main reasons for admissions were CRS (n=20, 83.3%) and ICANS (n=3, 12.5%). Fourteen patients (58.3%) required inotropic support, 14(58.3%) respiratory. Sixteen patients (66.6%) received tocilizumab, 10(41.6%) steroids, 6(25.0%) anakinra, and 5(20.8%) siltuximab. Ten patients (41.6 %) presented neurotoxicity, six of them severe (ICANS 3-4). Two patients died at PICU (8.3%) because of refractory CRShemophagocytic lymphohistyocitosis (carHLH) syndrome. There were no significant differences in relapse rate after CAR-T in patients requiring PICU, it was more frequently CD19 negative (p=0.344).Discussion: PICU admission after CAR-T therapy was mainly due to CRS. Supportive treatment allowed effective management and high survival. Some patients presenting with carHLH, can suffer a fulminant course.